Uniform convergence of the Fourier spherical sums differentiated by the function - Grona , V. L. (Ukrains’kyi Matematychnyi Zhurnal, 1991)
Asymptotic equalities are found for exact upper bounds of the deviations in the uniform metric of the spherical sums of a multiple trigonometric Fourier series on classes of functions with a mean-bounded Liouville derivative.